Tribes, Government and History in Yemen: By Paul Dresch. Oxford: Oxford University Press, 1989. (American Journal of Islam and Society, 1997)
This book is complex and, at points, obscure. Yet it is also an exceptionallyrich collection of information about trihal identity and ethos in Yemen and, forscholars with a special interest in Yemeni society, can be a valuable resource.The author orients much of his material toward two main questions, neither ofwhich I formulated explicitly: How can tribal political organization and statelegal institutions co-exist, not only for brief moments but for over 1,000 years?and How have the names and boundaries of tribal territories been preserved withlittle change for such a long time?The answer to the first question is on p. 165: " ... the hijrah [in YemeniArabic: a protected space or person] provided the point around which both statesof the world turned: strong Imams fheads of state] and weak. It could do so because it meant different things to different people.” The first 150 pages of thebook, especially chapters 2 (“The Language of Honour”), 3 (“Tribes andCollective Action”) and 4 (“Estates of Society within the Tribal Peace”), lead upto and persuaded us to accept the conclusion that the mutual recognition by thestate and by the tribes of neutral zones and people in tribal territories facilitatedtrade, tribe-state communication, and contact between literate Islamic specialistsand illiterate farmers and stock-breeders. Even when the interests of the tribesand the state were directly opposed (for instance, in controlling roads and determiningrates of taxation), violent conflicts between tribe and state were keptpartly in check by tribal custom, just as they were when tribe clashed with tribe(see pp. 267, 268, 379-387) ...